2022
DOI: 10.1007/s11764-022-01230-y
|View full text |Cite
|
Sign up to set email alerts
|

Decision aids for cancer survivors’ engagement with survivorship care services after primary treatment: a systematic review

Abstract: Purpose To elucidate existing decision aids (DAs) in supporting cancer survivors’ decisions to engage in cancer survivorship care services after primary treatment. Secondary objectives are to assess the DA acceptability, impact of DAs, and implementation barriers. Methods Databases (PubMed, Embase, PsycINFO, CINAHL) were searched to collect publications from inception through September 2021. Studies describing the development or evaluation of DAs used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(256 reference statements)
0
2
0
Order By: Relevance
“…In this view, patient autonomy is a widely recognised practice in treatment decision-making [ 20 , 21 ] and survivorship care. [ 22 ]…”
Section: Autonomymentioning
confidence: 99%
“…In this view, patient autonomy is a widely recognised practice in treatment decision-making [ 20 , 21 ] and survivorship care. [ 22 ]…”
Section: Autonomymentioning
confidence: 99%
“…All these would enable the healthcare users to make their informed choice on which treatment they should undergo. Previous reviews had demonstrated the effectiveness of decision aids in improving knowledge of healthcare users about the health condition they faced, and reducing their decisional conflict that they had in choosing treatment options, although variations did exist in the effect of decision aid utilisation on these outcomes across studies (Alarcon‐Ruiz et al, 2022; Ke et al, 2022; Knops et al, 2013; Paskins et al, 2020; Violette et al, 2015). These findings suggest that decision aids may help enhance the effectiveness of counselling services involving impartation of knowledge on healthcare services to counsellees and enable them to make informed choices on the utilisation of these services.…”
Section: Introductionmentioning
confidence: 99%